RP-UPLC method development and validation for quantitative analysis of antiemetic Trimethobenzamide hydrochloride - VM DHALAPE,; ST KHADANGALE,; RV PINJARI, (International Journal of Pharma and Bio Sciences, 2018)
Trimethobenzamide Hydrochloride (TMB·HCI), is an active pharmaceutical ingredient used as an antiemetic drug and synthesized in very huge quantity. A simple and rapid reverse phase ultra-performance liquid chromatographic (RP-UPLC) method for determination of TMB·HCI have been developed and validated using the ICH guideline. The effective chromatographic separations were achieved on Acquity CSH Phenyl-Hexyl, 2.1 x 100 mm 1.7µm column and reverse phase with linear gradient elution. The mobile phase-A is 0.1% Nonaflurobutane -1 sulfonic acid in water while mixture of 35:65 ratio of 0.1 % Nonaflurobutane -1-sulphonic acid in purified water with acetonitrile as mobile phase-B delivered flow rate 0.4 mL min−1 using PDA/UV detector. The column oven temperature is 40°C.The injection volume is 1.0μL.The method yields a well separated Trimethobenzamide (TMB) peak from the impurities. These impurity peaks are then identified. The degradation of TMB under various stress condition is studied. The total run time of the method is reduced to 5 mins i.e. to 25 % of reported method The new RP-UPLC method is precise, accurate as well as rapid and qualifies all the criteria of linearity, stability and robustness.